A Rare Variant in ERF (rs144812092) Predisposes to Prostate and Bladder Cancers in an Extended Pedigree - Cannon-Albright Lisa Anne; Teerlink Craig Carl; Stevens Jeff; Huang Franklin W.; Sipeky Csilla; Schleutker Johanna; Hernandez Rolando; Facelli Julio; Agarwal Neeraj; Trump Donald L. (MDPI, 2025)
Simple SummaryHere we applied a powerful predisposition candidate gene identification strategy to identify rare variants shared by two related bladder cancer cases who were members of pedigrees exhibiting a significant excess of bladder cancers. We sequenced the exomes of pairs of related bladder cancer cases belonging to high-risk bladder cancer pedigrees to identify rare, shared variants shared as candidates for predisposition. A rare, shared variant in ERF was also found to show significant association with bladder cancer risk in an independent population, was present in other prostate cancer-affected members in the pedigree, and showed evidence for altering the function of the associated protein. This evidence supports ERF (ETS2 Repressor Factor) as a bladder and prostate cancer predisposition gene.Pairs of related bladder cancer cases who belong to pedigrees with an excess of bladder cancer were sequenced to identify rare, shared variants as candidate predisposition variants. Candidate variants were tested for association with bladder cancer risk. A validated variant was assayed for segregation to other related cancer cases, and the predicted protein structure of this variant was analyzed. This study of affected bladder cancer relative pairs from high-risk pedigrees identified 152 bladder cancer predisposition candidate variants. One variant in ERF (ETS Repressing Factor) was significantly associated with bladder cancer risk in an independent population, was observed to segregate with bladder and prostate cancer in relatives, and showed evidence for altering the function of the associated protein. This finding of a rare variant in ERF that is strongly associated with bladder and prostate cancer risk in an extended pedigree both validates ERF as a cancer predisposition gene and shows the continuing value of analyzing affected members of high-risk pedigrees to identify and validate rare cancer predisposition variants.